The Influence of Director Leadership on Improvement of Creativeness Education Manpower, Productivity of Employee Education and Learning Success Students in Cirebon Maritime Academy - Siagian, Fereddy; Sirait, Jannes Eduard (Universitas Malikussaleh, 2019)
The elements in the management of education include elements of leaders, educators, educational staff , students and educational facilities as well as other supporters. All of these components are a unity that influences the quality of the learning process that can be seen from the success of students. The director as a leader at the Cirebon Maritime Academy has an influence on the creativity of educators, the work productivity of educational staff and the success of student learning. To find out the effect, survey research was conducted . Data collection techniques using documentation and questionnaire studies.The questionnaire was made in the form of a questionnaire with 5 alternative choices. Each alternative answers provided more aggressively weighted score of 1 - 5 (1 = strongly disagree, 2 = disagree, 3 = disagree, 4 = agree, and 5 = strongly agree ). Analysis of the data in this study consisted of (a) simple regression analysis; and (b) multiple analysis using statistical methods with the help of the SPSS 16 program. Regression analysis is used to predict research that includes variables X for Y1, Y2 and Y3. Simple Regression Analysis looks at Vaiabel Coefficients (Y1X) and (Y2X) and Y3X. This analysis is used to test the effect of each research variable. Based on the results of data analysis it can be concluded as a result of the research that the Leadership of the Director (X) on the Improvement of Educators' Creativity (Y1) is quite significant. The Leadership of the Director (X) on the Productivity of Education Workers (Y2) is also quite significant, and the results of the calculation of the influence of the Leadership of the Director (X) on Learning Success (Y3) are quite significant